Changes in Efficacy Indicators for Adalimumab Biosimilar Candidate (HS016) for the Treatment of Active Ankylosing Spondylitis at Various Time Points - Su, Jinmei; Li, Mengtao; He, Lan; Zhao, Dongbao; Wan, Weiguo; Liu, Yi; Xu, Jianhua; Xu, Jian; Liu, Huaxiang; Jiang, Lindi; Wu, Huaxiang; Zuo, Xiaoxia; et al. (Frontiers in Pharmacology, 2020)
Objectives: A phase III, 24-week Chinese clinical trial demonstrated that efficacy and safety outcomes of treatments with 40 mg/0.8 mL HS016 (n = 416) or adalimumab (n = 232) for active ankylosing spondylitis (AS) patients was comparable. In the present study, a subanalysis of the clinical trial was conducted to determine whether also individual efficacy indicators were comparable between HS016 and adalimumab. Methods: The individual efficacy indicators total and nocturnal back pain, global assessment of disease activity, swollen joint count, Maastricht Ankylosing Spondylitis Enthesitis Score, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, Bath ankylosing Spondylitis Metrology Index and chest expansion, were assessed at baseline and every 2 weeks during the treatment period. Results: This subanalysis revealed no significant difference between the patient groups treated with HS016 or adalimumab for any individual efficacy indicator investigated at any time point (all P > 0.05) beside faster total back pain score improvements in the adalimumab group on week 10, 12 and 22, which became equal at week 24. Among these indicators, chest expansion showed a significant increase at each time point compared with baseline, whereas all other efficacy indicators showed significant decreases compared with baseline at each time point (all P < 0.05). All efficacy indicators had increased or decreased rapidly by week 2, and the values continued to increase/decrease up to week 12, with subsequent smaller changes thereafter up to week 24 of treatment. Conclusion: The response trajectory of most individual efficacy indicators was comparable between HS016 and adalimumab at each time point during the 24 weeks of the trial.